Low-expansion porous silicon-carbon composite material, preparation method and application

By forming a uniform SEI film in the porous silicon pores and embedding carbon nanotubes, the problems of low efficiency and cycle performance attenuation of porous silicon-carbon composite materials are solved, and the low expansion characteristics of high conductivity and long cycles are achieved, which improves lithium ions Electrochemical properties of batteries.

CN119240705AActive Publication Date: 2025-01-03WANXIANG 123 CO LTD

Patent Information

Application Number
CN202411399779.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-03
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The first-time efficiency of porous silicon-carbon composite materials in lithium-ion batteries is low and the circulation performance is fast attenuated, mainly due to the uneven SEI film and the poor binding force of carbon nanotubes and silicon surfaces, resulting in poor electrochemical performance.

Method used

A uniform SEI film is formed in the porous silicon pores, and carbon nanotubes are embedded in the porous silicon particles, and then carbon coated. Low-expanded porous silicon-carbon composite materials are prepared by spray drying and vapor deposition to ensure the uniformity of the SEI film. and stability of carbon nanotubes.

Benefits of technology

It significantly improves the first-time efficiency and cycle stability of the material, enhances the conductivity, reduces the expansion rate, and improves the electrochemical performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240705A_ABST
    Figure CN119240705A_ABST
Patent Text Reader

Abstract

The invention discloses a low-expansion porous silicon-carbon composite material, a preparation method and application, and belongs to the technical field of lithium ion battery negative electrode materials. According to the low-expansion porous silicon-carbon composite material provided by the invention, lithium ions are anchored on the surface of the functionalized porous silicon, and an artificial SEI film is generated in situ on pores and the surface of the porous silicon by utilizing a liquid-phase precipitation reaction, so that the problem of non-uniform growth of the SEI film is solved; according to the porous silicon-carbon composite material disclosed by the invention, the carbon nanotubes are embedded among porous silicon particles, the porous silicon and the carbon nanotubes are bonded together by the first carbon source, and the porous silicon-carbon composite material is subjected to pore filling by a vapor deposition method, so that the problems of high specific surface area, low first efficiency and low conductivity of the porous silicon are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a low-expansion porous silicon-carbon composite material, a preparation method and an application thereof. Background Art

[0002] Silicon-carbon composite materials are expected to become a new generation of negative electrode materials under the demand for high energy density. The coating structure is the most typical structure of silicon-carbon composite materials. In short, by coating the surface of the active material silicon with a carbon layer, the silicon particles are prevented from directly contacting the electrolyte, the volume effect of silicon is alleviated, and its conductivity is enhanced. According to the coating structure and the morphology of silicon particles, common coating structures include core-shell type, yolk-shell type and porous type.

[0003] Porous silicon has a rich pore structure. Compared with conventional nano-silicon particles, the internal voids of silicon can provide a buffer space for material expansion and relieve the mechanical stress inside the material. At the same time, the pore structure can provide a fast ion transmission channel, making the material have better electrical performance. However, porous silicon has a large specific surface area, which will lead to processing difficulties and increase the risk of direct contact between silicon particles and electrolytes, consuming too many lithium ions to form SEI films, resulting in low first efficiency. In addition, silicon has low intrinsic conductivity, resulting in poor electronic conductivity.

[0004] In view of the above problems, the solution adopted is to construct an artificial SEI film on the surface of porous silicon to reduce the consumption of electrolyte, solve the irreversible capacity loss, and improve the coulombic efficiency of the material. Chinese patent CN117673287A treats porous silicon nano-sized and then granulates it and mixes it with lithium powder, dispersant, carbon source, etc. and then calcines it. By pre-lithiation and coating the surface of porous silicon, the first coulombic efficiency and cycle stability of lithium batteries are effectively improved. However, the solid phase mixing method is prone to uneven dispersion, and it is difficult to penetrate into the pores of porous silicon, which leads to uneven wrapping of the formed SEI film, which ultimately affects the electrochemical performance of the material.

[0005] Carbon nanotubes are one-dimensional carbon nanomaterials with the characteristics of good toughness and high electrical conductivity. Carbon nanotubes are compounded with porous silicon-carbon materials to improve the electrical conductivity of the material and enhance the electrochemical performance of the material. Chinese patent CN106058256A loads metal catalysts on a porous silicon substrate, and distributes carbon nanotubes inside and outside the porous silicon particles by chemical vapor deposition, thereby enhancing the overall electronic conductivity of the porous silicon, effectively increasing the reversible capacity of the silicon negative electrode material, and improving its electrochemical performance. However, carbon nanotubes are deposited on the surface of porous silicon by chemical vapor deposition, and the surface deposition uniformity of the carbon nanotubes and their surface bonding with silicon are poor, making them easy to fall off during the charge and discharge cycle. At the same time, the pores of porous silicon are difficult to fill, and there is a risk of direct contact with the electrolyte, resulting in low initial efficiency and rapid decay of cycle performance. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a silicon-carbon composite material in which a uniform SEI film is formed in the pores of porous silicon, carbon nanotubes are embedded in the interior of porous silicon particles, and then carbon is coated; another purpose of the present invention is to provide a low-expansion porous silicon-carbon composite material with high initial efficiency, high conductivity and long cycle.

[0007] The present invention discloses a method for preparing a low expansion porous silicon-carbon composite material, comprising the following steps:

[0008] S1 Preparation of functional porous silicon: placing silicon-aluminum alloy in an acid solution to react to obtain porous silicon, washing the porous silicon with water until it is neutral; then adding concentrated sulfuric acid and hydrogen peroxide mixed solution, stirring until the surface of the porous silicon is hydroxylated, washing with water, and drying to obtain functional porous silicon;

[0009] S2 pre-lithiates the surface of the functionalized porous silicon: the functionalized porous silicon obtained in step S1 is uniformly dispersed in water to form a uniform suspension, the suspension is mixed with a lithium acetate aqueous solution, and the suspension is fully reacted; then an ammonium fluoride aqueous solution is added, and the mixture is stirred until the reaction is complete to obtain a mixed solution;

[0010] S3: preparing a spray-dried precursor: uniformly mixing the mixed solution obtained in step S2 with the carbon nanotube dispersion; and then mixing with the first carbon source dispersion to form a uniform and stable precursor solution;

[0011] S4 spray drying: spray drying the precursor liquid obtained in step S3 to obtain a powder;

[0012] S5 High-temperature carbonization and pore filling with a second carbon source: The powder obtained in step S4 is carbonized at a high temperature in a protective gas atmosphere, and then a second carbon source is introduced to perform vapor deposition pore filling on the composite material, followed by cooling and sieving.

[0013] The aluminum element in the silicon-aluminum alloy is removed by acid solution to form porous silicon. The porous silicon is then added to a mixed solution of concentrated sulfuric acid and hydrogen peroxide to hydroxylate the surface of the porous silicon. The hydroxyl groups on the surface of the hydroxylated porous silicon will coordinate or chemically combine with lithium ions. After adding ammonium fluoride, the lithium ions will combine with fluoride ions to form a uniform LiF layer on the surface of the porous silicon and the surface of the pores through liquid phase deposition.

[0014] Furthermore, in step S1, the particle size of the silicon-aluminum alloy is 50-300nm, and the mass ratio of silicon to aluminum is 1:1-5; the acid solution is selected from hydrochloric acid and sulfuric acid, and the concentration is 10-30wt%; the reaction time is 6-24h; the mass ratio of concentrated sulfuric acid to hydrogen peroxide is 1-3:1, and the reaction time is 0.5-2h.

[0015] Furthermore, in step S2, the content of functionalized porous silicon in the suspension is 10-30wt%; the concentrations of the lithium acetate aqueous solution and the ammonium fluoride aqueous solution are both 5-20wt%, and the molar ratio of the added lithium acetate to ammonium fluoride is 1:1.

[0016] Furthermore, in step S2, the content of the porous silicon in the solid matter of the obtained mixed solution is 60-90wt%. The surface and pores of the silicon-carbon composite material form a uniform LiF layer while ensuring the performance of silicon-carbon.

[0017] The solid substance in the mixed liquid is porous silicon with LiF deposited on the surface, and an artificial SEI film is formed on the surface of the porous silicon.

[0018] Furthermore, in step S3, the diameter of the carbon nanotubes is 1-10 nm, and the length is 0.5-2 μm; the concentration of the carbon nanotubes in the carbon nanotube dispersion is 0.1-0.2 wt %; and the mass of the carbon nanotubes is 0.5-3% of the mass of the functionalized porous silicon.

[0019] The carbon nanotubes are wrapped by the first carbon source to strengthen the bonding force between the carbon nanotubes and the porous silicon, making them less likely to fall off during circulation.

[0020] Furthermore, in step S3, the dispersion solvents used to disperse the carbon nanotubes and the first carbon source are independently selected from one or more of acetone, isopropanol, toluene, heavy oil, tetrahydrofuran, and water.

[0021] Furthermore, in step S3, the first carbon source is selected from one or more of coal-based asphalt, petroleum asphalt, phenolic resin, furfural resin, and polyethylene glycol; the mass of the first carbon source is 1-10% of the mass of the functionalized porous silicon.

[0022] Furthermore, in the step S4, during the spray drying operation, the inlet temperature is 110-150° C., the feed rate is 0.1-5 L / h; and the particle size of the powder is controlled to be 3-15 μm.

[0023] Furthermore, in step S5, the high-temperature carbonization temperature is 800-1200°C, the heating rate is 5-20°C / min, and the insulation time is 1-2h; the second carbon source is selected from one of methane, ethane, propane, and acetylene; the flow rate of the second carbon source is 0.5-3L / min, and the introduction time is 1-5h.

[0024] Furthermore, in step S5, a rotary kiln is used for high-temperature carbonization; wherein the rotation speed of the rotary kiln is 0.3-1.5 r / min.

[0025] Furthermore, in step S5, the mesh size of the sieve is 200-350 meshes.

[0026] The pores of the carbonized porous silicon carbon are filled with carbon by vapor deposition, and the electrolyte is prevented from directly contacting the porous silicon.

[0027] The invention also discloses a low expansion porous carbon composite material, which is prepared by the preparation method described above.

[0028] The present invention also discloses a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte; the negative electrode sheet comprises the low-expansion porous silicon-carbon composite material as described above, and the initial efficiency is greater than 90%.

[0029] The low-expansion porous silicon-carbon composite material provided by the present invention anchors lithium ions on the functionalized porous silicon surface, and then utilizes a liquid phase precipitation reaction to in-situ generate an artificial SEI film in the pores and surface of the porous silicon, thereby solving the problem of uneven growth of the SEI film; carbon nanotubes are embedded between porous silicon particles, a first carbon source bonds the porous silicon and the carbon nanotubes together, and the porous silicon-carbon composite material is filled with pores by a vapor phase deposition method, thereby greatly improving the problems of high specific surface area, low initial efficiency, and low conductivity of the porous silicon. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a flow chart of the method for preparing the low expansion porous carbon composite material disclosed in the present invention;

[0031] Figure 2 It is a schematic diagram of the structure of the low expansion porous carbon composite material disclosed in the present invention;

[0032] Figure 3 is the XRD diagram of the low expansion porous silicon-carbon composite material of Example 1 of the present invention;

[0033] Figure 4 It is a graph showing the powder resistance test results of Example 1 and Comparative Examples 1-2 of the present invention;

[0034] Figure 5 This is a test diagram of the capacitive capacitance of the low expansion porous silicon-carbon composite material of Example 1 of the present invention;

[0035] Figure 6 It is a test chart of the electrical cycling of the porous silicon-carbon composite material of Example 1 and Comparative Examples 1 and 2 of the present invention. DETAILED DESCRIPTION

[0036] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0037] Example 1

[0038] Preparation of low expansion porous silicon-carbon composites:

[0039] S1: Take 10g of 100nm silicon-aluminum alloy (mass ratio of silicon to aluminum is 1:2) and place it in 100mL of 25wt% H2SO4 solution, stir it for 12h, and then wash it with water until it is neutral. Then slowly add it into 100mL of 98% concentrated H2SO4 and 30% H2O2 (mass ratio is 5:2) and treat it for 1h. After washing with water until it is neutral, vacuum dry it at 80℃ to obtain hydroxylated porous silicon powder.

[0040] S2: The hydroxylated porous silicon powder obtained in step S1 is added to deionized water to prepare a 10wt% suspension, and ultrasonically dispersed evenly. 29g of 10wt% lithium acetate aqueous solution is added, and after stirring for 2h, 16g of 10wt% NH4F aqueous solution is slowly added dropwise, and stirring is continued for 1h to obtain a mixed solution (porous silicon accounts for 90wt% and LiF accounts for 10wt% of the solid matter in the mixed solution).

[0041] S3: Slowly add 100 g of 0.1 wt% carbon nanotube dispersion (carbon nanotube diameter 5 nm, length 0.8 μm, dispersant is water) to the mixed solution, stir evenly, then add 40 g of 0.5 wt% phenolic resin isopropanol dispersion, and continue stirring until a uniform and stable precursor liquid is formed.

[0042] S4: The precursor liquid is atomized and dried, the inlet temperature is 120°C, the feed rate is 1L / h, and the particle size D50 of the obtained dry powder is controlled at 7-8μm.

[0043] S5: The dry powder was placed in a rotary kiln and introduced with argon gas. The speed of the rotary kiln was 0.5 r / min. The temperature was first raised to 900°C and kept at this temperature for 2 hours. Then acetylene (flow rate 1 L / min) was introduced for 1 hour. The temperature was then lowered and the mixture was passed through a 300-mesh sieve to obtain a low-expansion porous silicon-carbon composite material.

[0044] Example 2

[0045] Preparation of low expansion porous silicon-carbon composites:

[0046] S1: Place 10g of 150nm silicon-aluminum alloy (mass ratio of silicon to aluminum is 1:2) in 100mL of 25wt% HCl solution, stir for 12h, and then wash with water until neutral. Then slowly add it into 100mL of 98% concentrated H2SO4 and 30% H2O2 (mass ratio is 7:3) for 0.5h, wash with water until neutral, and dry it at 80℃ in vacuum to obtain hydroxylated porous silicon powder.

[0047] S2: The hydroxylated porous silicon powder obtained in step S1 is added to deionized water to prepare a 12wt% suspension, and ultrasonically dispersed evenly. 29g of 10wt% lithium acetate aqueous solution is added, and after stirring for 2h, 16g of 10wt% NH4F solution is slowly added dropwise, and stirring is continued for 1h to obtain a mixed solution (porous silicon accounts for 90wt% and LiF accounts for 10wt% of the solid matter in the mixed solution).

[0048] S3: Slowly add 27 g of 0.3 wt% carbon nanotube dispersion (carbon nanotube diameter 3 nm, length 1 μm, dispersion solvent is water) to the mixed solution, stir evenly, then add 40 g of 0.5 wt% petroleum asphalt isopropanol dispersion, and continue stirring until a uniform and stable precursor liquid is formed.

[0049] S4: The precursor liquid is spray dried, the inlet temperature is 110°C, the feed rate is 1.2L / h, and the particle size D50 of the obtained dry powder is controlled at 7-8μm.

[0050] S5: Place the dry powder in a rotary kiln and introduce argon. The speed of the rotary kiln is 0.3 r / min. First, heat it to 850°C and keep it warm for 2 hours. Then introduce acetylene (flow rate 1 L / min) and continue for 1.5 hours before cooling it down. Pass it through a 300-mesh sieve to obtain a low-expansion porous silicon-carbon composite material.

[0051] Example 3

[0052] Preparation of low expansion porous silicon-carbon composites:

[0053] S1: Place 12g of 100nm silicon-aluminum alloy (mass ratio of silicon to aluminum is 1:2.5) in 100mL of 20% H2SO4 solution, stir for 15h, and then wash with water until neutral. Slowly add it into 100mL of 98wt% concentrated H2SO4 and 30wt% H2O2 (mass ratio is 7:3) for 1h, wash with water until neutral, and dry it at 80℃ in vacuum to obtain hydroxylated porous silicon powder.

[0054] S2: Add hydroxylated porous silicon powder to deionized water to prepare an 8wt% suspension, disperse it evenly by ultrasonication, add 19g of 15wt% lithium acetate solution, stir for 1.5h, then slowly add 10.5g of 15wt% NH4F solution, continue stirring for 1h, and obtain a mixed solution (porous silicon accounts for 88wt% and LiF accounts for 12wt% of the solid matter in the mixed solution).

[0055] S3: Slowly add 150g of 0.1wt% carbon nanotube dispersion (the carbon nanotube has a diameter of 4nm and a length of 1μm, the dispersion solvent is water, and the carbon tube is 1.5wt% of the porous silicon mass) into the mixed solution, stir evenly, then add 30g of 1wt% phenolic resin ethanol dispersion, and continue stirring until a uniform and stable precursor liquid is formed.

[0056] S4: The precursor liquid is spray dried, the inlet temperature is 120°C, the feed rate is 0.8L / h, and the particle size D50 of the obtained dry powder is controlled at 7-8μm.

[0057] S5: The dry powder was placed in a rotary kiln and introduced with argon gas at a speed of 0.3 r / min. The temperature was first raised to 950°C and kept at this temperature for 2 h. Acetylene (flow rate 1 L / min) was then introduced for 0.5 h. The powder was cooled and passed through a 300-mesh sieve to obtain a low-expansion porous silicon-carbon composite material.

[0058] like Figure 1-2 As shown, an artificial SEI film (LiF) is formed by in-situ reaction on the surface of the porous silicon particles and the surface of the pores. The first carbon source bonds the porous silicon particles to the carbon nanotubes, and secondary particles are formed by spray drying. After carbonization, the secondary particles are filled with pores by vapor deposition.

[0059] Comparative Example 1

[0060] Preparation of silicon-carbon composite materials:

[0061] 1) Take 10g of 100nm silicon-aluminum alloy (mass ratio of silicon to aluminum is 1:2) and place it in 100mL of 25wt% H2SO4 solution, stir it for 12h, and then wash it with water until it is neutral. Then slowly add it into 100mL of 98wt% concentrated H2SO4 and 30% H2O2 (mass ratio is 5:2) for 1h, wash it with water until it is neutral, and dry it at 80℃ in vacuum to obtain hydroxylated porous silicon powder.

[0062] 2) Prepare the hydroxylated porous silicon powder into a 10% emulsion, disperse it evenly by ultrasonication, slowly add 100 g of 0.1% carbon nanotube dispersion (carbon nanotube diameter 5 nm, length 0.8 μm, dispersion solvent is water), stir evenly, then add 40 g of 0.5 wt% phenolic resin isopropanol dispersion, and continue stirring until a uniform and stable precursor liquid is formed.

[0063] 4) The precursor liquid was spray dried, the inlet temperature was 120°C, the feed rate was 1L / h, and the particle size D50 of the obtained dry powder was controlled at 7-8μm.

[0064] 5) The dry powder was placed in a rotary kiln and introduced with argon gas at a speed of 0.5 r / min. The temperature was first raised to 900°C and kept at this temperature for 2 h. Acetylene (flow rate 1 L / min) was then introduced for 1 h. The temperature was then lowered and the porous silicon-carbon composite material was obtained by passing through a 300-mesh sieve.

[0065] Comparative Example 2

[0066] Preparation of silicon-carbon composite materials:

[0067] 1) Take 10g of 100nm silicon-aluminum alloy (mass ratio of silicon to aluminum is 1:2) and place it in 100mL of 25wt% H2SO4 solution, stir it for 12h, and then wash it with water until it is neutral. Then slowly add it into 100mL of 98wt% concentrated H2SO4 and 30wt% H2O2 (mass ratio is 5:2) for 1h, wash it with water until it is neutral, and dry it at 80℃ in vacuum to obtain hydroxylated porous silicon powder.

[0068] 2) Add hydroxylated porous silicon powder to deionized water to prepare a 10wt% suspension, disperse it evenly by ultrasonication, add 29g of 10wt% lithium acetate solution, stir for 2h, then slowly add 16g of 10wt% NH4F solution, continue stirring for 1h to obtain a mixed solution (porous silicon accounts for 90wt% and LiF accounts for 10wt% of the solid matter in the mixed solution).

[0069] 3) Add 40 g of 0.5% phenolic resin isopropanol dispersion (phenolic resin is 2% of the mass of porous silicon) to the mixed solution, and continue stirring until a uniform and stable precursor solution is formed.

[0070] 4) The precursor liquid was spray dried, the inlet temperature was 120°C, the feed rate was 1L / h, and the particle size D50 of the obtained dry powder was controlled at 7-8μm.

[0071] 5) The dry powder was placed in a rotary kiln and introduced with argon gas at a speed of 0.5 r / min. The temperature was first raised to 900°C and kept at this temperature for 2 h. Acetylene (flow rate 1 L / min) was then introduced for 1 h. The temperature was then lowered and the porous silicon-carbon composite material was obtained by passing through a 300-mesh sieve.

[0072] Performance Test:

[0073] The low expansion porous silicon-carbon composite material obtained in Example 1 was subjected to X-ray powder diffraction test. The results are as follows: Figure 3 shown.

[0074] The porous silicon-carbon composite materials prepared in Example 1 and Comparative Examples 1-2 were subjected to a powder resistance test. The test results are as follows: Figure 4 shown.

[0075] The porous silicon-carbon composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were prepared into a 2032 button battery for evaluation. The specific scheme was that the prepared material, conductive agent SP, conductive agent VGCF, and binder LA136 were mixed in a mass ratio of 75:5:10:10, and water was used as a solvent to coat the slurry on a copper foil. The counter electrode was a lithium sheet, and the separator was a Celgard 2400 microporous polypropylene film. The charge and discharge cut-off voltage was 0.005-1.5V, the discharge rate was first 0.1C to 0.005V, and then 0.02C to 0.005V, so that it was fully discharged, and the charge rate was 0.1C to charge to 1.5V. The test results of various properties are shown in Table 1.

[0076] Table 1: Test results of power-off of Examples 1-4 and Comparative Examples 1-2

[0077] Material Electrode resistance (Ω) Pole swelling rate (%) First lithium insertion capacity (mAh / g) First lithium removal capacity (mAh / g) First efficiency (%) Example 1 0.010 15.3 2110 1942.4 92.06 Example 2 0.011 14.8 2076.2 1894.7 91.26 Example 3 0.011 14.5 2067.8 1900 91.88 Comparative Example 1 0.012 20.4 2018.3 1702.6 84.34 Comparative Example 2 0.021 18.6 2039.6 1828.5 89.65

[0078] Result analysis:

[0079] from Figure 3 It can be seen that the structure of the low-expansion porous silicon-carbon composite material prepared in Example 1 is mainly the structure of crystalline silicon.

[0080] like Figure 4 As shown, Example 1 has a lower resistivity than Comparative Examples 1-2, and the resistivity of Example 1 is more significantly reduced than that of Comparative Example 2. This shows that adding carbon nanotubes between porous silicon particles can greatly improve the conductivity of the silicon-carbon composite material.

[0081] like Figure 5 As shown, Example 1 exhibits a high first lithium deintercalation capacity, a 1.5V lithium deintercalation capacity of 1942.4 mAh / g, and a first efficiency of 92.06%.

[0082] like Figure 6 As shown, compared with Comparative Examples 1-2, the capacity retention rate of Example 1 is significantly improved.

[0083] As shown in Table 1, compared with comparative examples 1-2, the electrode swelling rate of embodiments 1-3 is greatly reduced, and the first lithium insertion capacity, the first lithium removal capacity and the first efficiency are greatly improved.

[0084] Although the electrode resistance of Comparative Example 1 is not much different from that of Example 1, since LiF is not deposited on the surface of the porous carbon and the surface of the pores in Comparative Example 1, the electrode swelling rate, the first lithium insertion capacity, the first lithium removal capacity and the first efficiency are significantly worse.

[0085] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a low expansion porous silicon-carbon composite material, characterized in that: The following steps are involved: S1 Preparation of functional porous silicon: placing silicon-aluminum alloy in an acid solution to react to obtain porous silicon, washing the porous silicon with water until it is neutral; then adding concentrated sulfuric acid and hydrogen peroxide mixed solution, stirring until the surface of the porous silicon is hydroxylated, washing with water, and drying to obtain functional porous silicon; S2 pre-lithiates the surface of the functionalized porous silicon: the functionalized porous silicon obtained in step S1 is uniformly dispersed in water to form a uniform suspension, the suspension is mixed with a lithium acetate aqueous solution, and the suspension is fully reacted; then an ammonium fluoride aqueous solution is added, and the mixture is stirred until the reaction is complete to obtain a mixed solution; S3: preparing a spray-dried precursor: uniformly mixing the mixed solution obtained in step S2 with the carbon nanotube dispersion; and then mixing with the first carbon source dispersion to form a uniform and stable precursor solution; S4 spray drying: spray drying the precursor liquid obtained in step S3 to obtain a powder; S5 High-temperature carbonization and pore filling with a second carbon source: The powder obtained in step S4 is carbonized at a high temperature in a protective gas atmosphere, and then a second carbon source is introduced to perform vapor deposition pore filling on the composite material, followed by cooling and sieving.

2. The method for preparing a low expansion porous silicon-carbon composite material according to claim 1, characterized in that: In the step S1, the particle size of the silicon aluminum alloy is 50-300nm, the mass ratio of silicon to aluminum is 1:1-5; the acid solution is selected from hydrochloric acid and sulfuric acid, and the concentration is 10-30wt%; the reaction time is 6-24h; the mass ratio of concentrated sulfuric acid to hydrogen peroxide is 1-3:1, and the reaction time is 0.5-2h.

3. The method for preparing a low expansion porous silicon-carbon composite material according to claim 1, characterized in that: In the step S2, the content of the functionalized porous silicon in the suspension is 10-30wt%; the concentrations of the lithium acetate aqueous solution and the ammonium fluoride aqueous solution are both 5-20wt%, and the molar ratio of the added lithium acetate to ammonium fluoride is 1:

1.

4. The method for preparing a low expansion porous silicon-carbon composite material according to claim 1, characterized in that: In the step S3, the concentration of carbon nanotubes in the carbon nanotube dispersion is 0.1-0.2wt%; the diameter of the carbon nanotubes is 1-10nm, and the length is 0.5-2μm; the mass of the carbon nanotubes is 0.5-3% of the mass of the functionalized porous silicon.

5. The method for preparing a low expansion porous silicon-carbon composite material according to claim 1, characterized in that: In the step S3, the dispersion solvents used to disperse the carbon nanotubes and the first carbon source are independently selected from one or more of acetone, isopropanol, toluene, heavy oil, tetrahydrofuran, and water.

6. The method for preparing a low expansion porous silicon-carbon composite material according to claim 5, characterized in that: In step S3, the first carbon source is selected from one or more of coal-based asphalt, petroleum asphalt, phenolic resin, furfural resin, and polyethylene glycol; the mass of the first carbon source is 1-10% of the mass of the functionalized porous silicon.

7. The method for preparing a low expansion porous silicon-carbon composite material according to claim 1, characterized in that: In the step S4, during the spray drying operation, the inlet temperature is 110-150°C, the feed rate is 0.1-5L / h; and the particle size of the powder is controlled at 3-15μm.

8. The method for preparing a low expansion porous silicon-carbon composite material according to claim 1, characterized in that: In step S5, the high-temperature carbonization temperature is 800-1200°C, the heating rate is 5-20°C / min, and the insulation time is 1-2h; the second carbon source is selected from one of methane, ethane, propane, and acetylene; the flow rate of the second carbon source is 0.5-3L / min, and the introduction time is 1-5h.

9. A low expansion porous carbon composite material, characterized in that: The method is prepared according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the negative electrode sheet comprises the low expansion porous silicon-carbon composite material as described in right 9, and the initial efficiency is greater than 90%.

Citation Information

Patent Citations

  • Preparation method of carbon nanotube composite porous silicon anode material for lithium ion battery

    CN106058256A

  • Pre-lithiated silicon-based negative electrode material and preparation method thereof, negative electrode and battery

    CN117673287A

  • Porous silicon / carbon composite material and preparation method thereof

    CN102208634A

  • Porous silicon-carbon composite cathode material as well as preparation method thereof and lithium ion battery

    CN107994225A

  • Porous silicon negative electrode material for lithium ion battery and preparation method thereof

    CN111628162A

Cited By

  • Preparation method and application of low-expansion silicon-carbon negative electrode material

    CN119528146A